The Influence of Emotional Intelligence, Integrity, and Interpersonal Communication on Employee Performance - Faridah, Zaitun; Mallongi, Syahrir; Mapparenta, M. (Golden Ratio of Data in Summary, 2025)
This study examines the influence of Emotional Intelligence, Integrity, and Interpersonal Communication on the performance of employees at the Representative Office of the National Population and Family Planning Agency of South Sulawesi Province. The data in this study were obtained from employees at the Representative Office of the National Population and Family Planning Agency of South Sulawesi Province in 2025 who were willing to participate as respondents.This study uses primary data by conducting direct field research, distributing questionnaires/statements to respondents, and determining the sample size using the Slovin formula, resulting in 94.35. This means the researcher requires 94.35 samples for this study, which will be rounded to 95 respondents. Data analysis techniques include descriptive statistical analysis and SPSS 26.0. The hypothesis testing results show that emotional intelligence positively and significantly influences employee performance, indicating that the better the emotional intelligence is, the higher the employee's performance will be. Integrity also has a positive and significant influence on Employee Performance, meaning that the higher the Integrity, the better the performance of employees at the Representative Office of the National Population and Family Planning Agency of South Sulawesi Province. Similarly, Interpersonal Communication positively and significantly influences Employee Performance, implying that better Interpersonal Communication leads to improved employee performance at the Representative Office of the National Population and Family Planning Agency of South Sulawesi Province.